Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Prove that $\sqrt{n} > \ln n$ for all $n \in \mathbb{N}$.

I need to use this fact for one of the proofs that I am working on. However, I am having trouble proving this. I tried induction but don't really know how to do it. Can someone help me with this?

share|cite|improve this question

The most important inequality about the exponential is $$\tag1e^x\ge 1+x\qquad\text{for all }x\in\mathbb R\text{ with equality iff }x=0.$$ From this we find $$\tag2 e^{x}=(e^{x/2})^2\stackrel{(a)}\ge (1+x/2)^2=(1-x/2)^2+2x\stackrel{(b)}\ge 2x$$ where $(a)$ holds for $x\ge-2$ and is strict for $x\ne0$, and $(b)$ is strict for $x\ne 2$. Hence $e^{x}>2x$ at least for $x\ge-2$ and in fact trivially from $2x<0<e^x$ also for $x<-2$. By squaring $e^{2x}>4x^2$ for all $x\ge 0$, i.e. $$\tag3 e^x>x^2\qquad\text{for all }x\ge0.$$ With $x=\sqrt n>0$ and taking logarithms on both sides we get $$ \sqrt n>\ln n\qquad\text{for all }n>0.$$

share|cite|improve this answer
how to u get to 3? why e^2x becomes e^x? – Aha Apr 20 '14 at 12:44
Because since $e^{2x} > 4x^2 = 2x \cdot 2x = (2x)^2 $, then we can put $y = 2x$ and we obtain $e^y > y^2 $ – ProbabilityGuy Apr 24 '14 at 4:37
I don't understand this post, in that sense that how do you prove the "important" inequality? I am presuming you just do what Dutta's post does, and differentiate... – user1729 Apr 28 '14 at 11:59

Consider the function $f(x) = \sqrt x - \log x$ and differentiate: $$f'(x) = \frac{1}{2 \sqrt x} - \frac{1}{x} = \frac{\sqrt x - 2}{2x}. $$ Hence $f'(x) \le0$ for all $0\lt x\le4$ and $f'(x)\ge 0$ for all $x \ge 4$. So the function is monotone decreasing for all $0\lt x \le 4$ and monotone increasing for all $x \ge 4$.

Also $f(4) = \sqrt 4 - \log4=2-2\log2=2\log(\mathrm e/2) > 0$.

Thus $f(x) > 0$ for all $x \gt0$, that is, $\sqrt x - \log x > 0$.

Now put $x = n $ and get your result.

share|cite|improve this answer
Do you happen to know any non-calculus way of doing this? thanks – Aha Apr 20 '14 at 8:40
I do not know. Hope some other people will come with answer. – Dutta Apr 20 '14 at 8:45
thanks anyway :) – Aha Apr 20 '14 at 8:46
Actually $f$ is only increasing on $(4,+\infty)$, not on $(1,+\infty)$. Thus the argument can be saved, but it needs to be modified. // @upvoters Why the upvote? – Did Apr 20 '14 at 9:21
@derivative Thank you for identifying it. My mistake and same mistake has done by many people. – Dutta Apr 20 '14 at 9:36

Notice that $$\frac{\ln(n)}{\sqrt{n}} = 2 \frac{\ln(\sqrt{n})}{\sqrt{n}},$$ so it is sufficient to show that $$\frac{\ln(x)}{x}< \frac{1}{2} \ \text{for all} \ x >0 \hspace{1cm} (1)$$

If $f(x)= \frac{\ln(x)}{x}$ then $f'(x)= \frac{1-\ln(x)}{x^2}$, so $f$ is nondecreasing on $(0,e]$ and nonincreasing on $[e,+ \infty)$. Therefore, $f$ has a global maximum at $x=e$. Because $f(e)= \frac{1}{e} < \frac{1}{2}$, $(1)$ may be deduced.

share|cite|improve this answer

let $\sqrt n > \ln n$, then $$\sqrt{n+1} > \sqrt{(\log n)^2-( \log(n+1))^2+( \log(n+1))^2+1}> \log (n+1) $$ hence proved by induction, that is if we show that
$$\log(n)^2 - \log(n+1)^2 + 1 > 0$$ which you can find the maximum using calculus which is less than $1$. Also you can try this, \begin{align*} \log(n+1)^2 - \log(n)^2 &= (\log n + \log(1 +1/n))^2 - \log(n)^2\\ &= 2 \log(1 + 1/n) \log n+ \log(1+1/n)^2\\ &\le 2 \left( \frac 1 n \right ) \log n +\left( \frac 1 n \right )^2\\ & < 2 \left( \frac 1 n \right ) \sqrt n +\left( \frac 1 n \right )^2 \\ & <1 \; \forall n>5 \end{align*}

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.